At the threshold: A case study of a partnership between a student organization and an educational development center - Doktor, Stephanie DeLane; Bach, Dorothe; Abbot, Sophia; Hardin, Jacob (International Journal for Students as Partners, 2019)
This article offers a case study about the collaboration between a student-led organization and an academic development unit dedicated to improving teaching and learning at [Institution 2]. We describe the genesis of our collaboration, how we nurtured and developed it over time into a substantive program, and what we learned in the process. While most existing case studies focus on partnerships between students and faculty, we turn the lens inward and investigate the challenges involved in enacting an “ethic of reciprocity” (Cook-Sather and Felten, 2017) in a partnership between an academic development center and a student organization. Using the analytical framework of threshold concepts, we explore the rocky navigating of issues of trust, vulnerability, role confusion, the notion of expertise, and pre-existing power inequalities to move towards a more collaborative and equitable partnership.